Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4103/jfmpc.jfmpc_1921_21
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum ferritin with COVID-19 in a cross-sectional study of 200 intensive care unit patients in a rural hospital

Abstract: Background: The COVID-19 disease caused by the SARS-CoV-2 virus, has toppled the world since first case noted in 2019, and the cases have been increasing there after. This grave effect is caused by the cytokine storm induced inflammation produced by the noxious virus. As it is an inflammatory state, various acute phase reactants are expected to raise; thus serum ferritin is contemplated to increase. Here we aim to anchor serum ferritin as a way marker for diagnosis and management of COVID-19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Patients with raised LDH in mild CT score were 21 out of 27 (77.77%), in moderate CT score (11)(12)(13)(14)(15) were 27 out of 27(100%), in severe CT score (16)(17)(18)(19)(20) were 34 out of 34 (100%), in very severe CT scores were 9 out of 12(75%). HRCT Score and LDH showed positive correlation (r-0.26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with raised LDH in mild CT score were 21 out of 27 (77.77%), in moderate CT score (11)(12)(13)(14)(15) were 27 out of 27(100%), in severe CT score (16)(17)(18)(19)(20) were 34 out of 34 (100%), in very severe CT scores were 9 out of 12(75%). HRCT Score and LDH showed positive correlation (r-0.26).…”
Section: Resultsmentioning
confidence: 99%
“…Various authors also studied these and reported similar findings. They are Padiya G S et al, 11 Kömürcüoglu B et al, 12 Sharma S. et al, 3 Vidyashree S et al, 13 Gupta P et al, 14 Padiya G S et al 11 did a study on 59 patients which included 21 patients in the mild group,31 in the moderate group, and 7 in the severe group. CT severity score was found to be positively correlated with ferritin levels (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…I read with great interest the study by Hulkoti and colleagues reporting that a high concentration of serum ferritin was a prognostic marker in severe coronavirus disease (COVID-19). [ 1 ] As they stated,[ 1 ] ferritin has tended to be a forgotten marker among markers relevant to clinical decision-making concerning COVID-19; therefore, their finding of ferritin is unique. As measuring ferritin is readily performed and relatively inexpensive, their idea of including ferritin in clinical practice for COVID-19 cases[ 1 ] also appears quite useful.…”
mentioning
confidence: 99%
“…[ 1 ] As they stated,[ 1 ] ferritin has tended to be a forgotten marker among markers relevant to clinical decision-making concerning COVID-19; therefore, their finding of ferritin is unique. As measuring ferritin is readily performed and relatively inexpensive, their idea of including ferritin in clinical practice for COVID-19 cases[ 1 ] also appears quite useful. Further studies should be conducted to determine the correlation of ferritin levels with the severity and cut-off levels of ferritin for identifying the likelihood of critical outcomes in patients with COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation